2019
DOI: 10.1016/j.cell.2019.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Mechanoelectrical Transduction: Structure and Function of Force-Gated Ion Channels

Abstract: The conversion of force into an electrical cellular signal is mediated by the opening of different types of mechanosensitive ion channels (MSCs), including TREK/TRAAK K 2P channels, Piezo1/2, TMEM63/OSCA and TMC1/2. Mechanoelectrical transduction plays a key role in hearing, balance, touch, proprioception and is also implicated in the autonomic regulation of blood pressure and breathing. Thus, dysfunction of MSCs is associated with a variety of inherited and acquired disease states. Significant progress has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(142 citation statements)
references
References 112 publications
(205 reference statements)
2
139
0
1
Order By: Relevance
“…The mechanically activated Piezo channel, including Piezo1 and Piezo2 (Coste et al, 2010;Coste et al, 2012), represent a class of versatile mechanotransducers for mediating distinct forms of mechanical stimuli in a wide variety of cell types and consequently governing a broad spectrum of biological processes (Douguet and Honore, 2019;Murthy et al, 2017;Wu et al, 2016;Xiao, 2019). Elucidating its mechanogating mechanism is fundamental to understand how it might fulfill its mechanotransduction function in intact cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanically activated Piezo channel, including Piezo1 and Piezo2 (Coste et al, 2010;Coste et al, 2012), represent a class of versatile mechanotransducers for mediating distinct forms of mechanical stimuli in a wide variety of cell types and consequently governing a broad spectrum of biological processes (Douguet and Honore, 2019;Murthy et al, 2017;Wu et al, 2016;Xiao, 2019). Elucidating its mechanogating mechanism is fundamental to understand how it might fulfill its mechanotransduction function in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular mechanotransduction process requires designated mechanotransducers to convert mechanical force into various fundamental biological activities, ranging from cellular division, differentiation and migration to physiological sensing of blood pressure, touch, mechanical pain, balance and sound (Chalfie, 2009;Douguet and Honore, 2019;Jin et al, 2020;Katta et al, 2015;Leckband and de Rooij, 2014;Lecuit and Yap, 2015;Niessen et al, 2011). Adhesion molecules and mechanosensitive ion channels represent two major types of mechanotransducers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…K2P2.1 (TREK-1) is the founding member of the thermo-and mechanosensitive subgroup of K2Ps (Douguet and Honore, 2019;Feliciangeli et al, 2014). Although this channel is resistant to RuR inhibition ( Figure 1B and D, Table 1) (Braun et al, 2015), two electrode voltage clamp (TEVC) recordings in Xenopus oocytes of outward current inhibition by RuR under physiological ionic conditions showed that installation of a point mutation I110D at the base of the K2P2.1 (TREK-1) CAP domain conferred sub-micromolar RuR sensitivity to K2P2.1 (TREK-1) (IC50 = 0.287 ± 0.054 µM)(Figs.…”
Section: A Single Site In the K2p Cap Domain Confers Rur Sensitivitymentioning
confidence: 99%